2021
DOI: 10.1186/s13068-021-02014-9
|View full text |Cite
|
Sign up to set email alerts
|

Function of ORFC of the polyketide synthase gene cluster on fatty acid accumulation in Schizochytrium limacinum SR21

Abstract: Background As a potential source of polyunsaturated fatty acids (PUFA), Schizochytrium sp. has been widely used in industry for PUFA production. Polyketide synthase (PKS) cluster is supposed to be the primary way of PUFA synthesis in Schizochytrium sp. As one of three open reading frames (ORF) in the PKS cluster, ORFC plays an essential role in fatty acid biosynthesis. However, the function of domains in ORFC in the fatty acid synthesis of Schizochytrium sp. remained unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 60 publications
5
17
0
Order By: Relevance
“…Knockout of ER B significantly decreased the content of PUFAs in S. limacinum SR21. Knockout of ER C reduced the content of SFAs, while overexpression of ER C led to a decrease in PUFA content and an increase in SFA content in S. limacinum SR21 (Ling et al, 2020;Shi et al, 2021). In addition, several lines of evidence have demonstrated that the addition of triclosan can inhibit the expression of ER C and lead to an increase in PUFA production (Ling et al, 2020).…”
Section: Enoyl-acp Reductase Domainmentioning
confidence: 99%
See 3 more Smart Citations
“…Knockout of ER B significantly decreased the content of PUFAs in S. limacinum SR21. Knockout of ER C reduced the content of SFAs, while overexpression of ER C led to a decrease in PUFA content and an increase in SFA content in S. limacinum SR21 (Ling et al, 2020;Shi et al, 2021). In addition, several lines of evidence have demonstrated that the addition of triclosan can inhibit the expression of ER C and lead to an increase in PUFA production (Ling et al, 2020).…”
Section: Enoyl-acp Reductase Domainmentioning
confidence: 99%
“…The heterologous expression of PUFA synthase in E. coli showed that the mutation or deletion of DH FabA -1 or substitution of DH FabA -1 with DH FabA -2 led to the loss of PUFA production capacity, and the mutation or deletion of DH FabA -2 led to a small amount of DPA production and no DHA production ( Xie et al, 2020 ). The overexpression of the DH FabA -1 domain in S. limacinum SR21 increased the content of PUFAs and total lipids ( Shi et al, 2021 ). Disruption of the DH FabA -2 domain of Schizochytrium sp.…”
Section: Function Of Domains In Eukaryotic Pufa Synthasementioning
confidence: 99%
See 2 more Smart Citations
“…22 μm syringe filter (Anpel, China) to remove impurities. The carotenoids were analyzed by HPLC (1200 series, Agilent Technologies) equipped with a YMC C30 column (250 mm × 4.6 mm i.d.…”
mentioning
confidence: 99%